The Impact of Venture Capital Investment on the Strategic Decisions and Operations of Social Startups - Sargsyan, Marianna; Lukeš, Martin, 1976-; Polychronopoulos, Georgios; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The following paper studies the impact that venture capital investment has on social startups' strategic decisions and operations. To answer the research questions, six areas of a growing startup are identified and discussed: strategy and managerial processes, hiring, finances, innovation, leadership, and scaling. Qualitative semi-structured interviews are conducted with 10 founders and CEOs, who provide their perspectives on the research topic. The paper applies coding and categorizing to derive the results by visualizing the outcomes. The findings show that the impact investment influences the performance of startups along the identified six areas, which can be evident across a time frame. The research also finds more positive aspects of investments and that social startups can develop lasting relationships with their investors. The paper concludes with four propositions and suggestions for future research.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses